Management of Long-Distance Marriage for Overseas Female Worker Profession on Family Resilience in Kendal Regency - Filda Rahma Saidah; Muhammad Zaki Fahmi (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2023)
Long-distance marriage relationship for female worker profession (Tenaga Kerja Wanita: TKW) who works abroad is a condition where husband and wife are constrained by distance and time to meet. These obstacles resulted in short meetings that were felt to be lacking so they lost the figure of a partner and wanted to get back together. This study aims to analyze the management of long-distance marriages for women who work as workers abroad in family resilience in the Kendal district. This research is empirical legal research using primary data sources. The data is filtered using data triangulation techniques. Then analyzed using Al-Buthi's maslahah theory and Talcott Parsons' structural-functional theory. The results of this study indicate that overseas female worker profession (TKW) in the Kendal Regency community carry out long-distance marriage management with various things so that they can strengthen their families in several steps, namely; there is communication, trust, and commitment, and there is a meeting schedule. According to the structural-functional theory, it has fulfilled the elements of adaptation, goal attainment, integration, and latency. Meanwhile, according to maslahah theory, it does not conflict with maslahah if it is considered an emergency in the field of work and the main goal is hifz an-nasl, but it can conflict if it is only for the sake of material pleasure in terms of collecting wealth.